The making of The Wizard of Oz - Harmetz, Aljean (Chicago Review Press, 2013)
Released in conjunction with the 75th-anniversary DVD release of The Wizard of Oz, this book is the definitive story of how one of America's most beloved movies was made and a marvelous, unprecedented examination of how Hollywood used to make movies. This updated edition includes numerous photos and shares hundreds of interviews with cameramen, screenwriters, costume designers, directors, producers, light technicians, actors, and more to reveal how the factory-like Hollywood system of moviemaking miraculously produced one of the most enduring films ever made. From the scandalous headlines of Munchkin orgies at the Culver City Hotel and the Witch's (accidental) burning to the building of the Emerald City and the sewing of nearly 1,000 costumes, The Making of The Wizard of Oz provides a richly detailed re-creation of MGM's production No. 1060 and a detail-by-detail, department-by-department look at the most powerful and flamboyant studio Hollywood has ever known.